Salmonella enteric server Typhi multidrug resistant to antibiotics and a study of the effect of age and sex on the incidence of typhoid fever (Journal of the College of Basic Education, 2022)
) 335) samples were collected blood from Ibn-albaldy Hospital and Imam Ali Hospital, kinady Hospital and the ALwiyah Children's Hospital and Fatima Zahra Hospital from Baghdad and Erbil Teaching Hospital and Hospital Hawija of Kirkuk and the Central Health Laboratory in Sulaimaniyah. Patients with questionable typhoid fever Undergone all the samples to blood cultures, especially the samples gave positive results for checking Al –we dil test The) 180( case is positive and there are two way for cultures blood (brain heart infusion bottle] and gave) 21) cases of positive All samples to examine drug sensitivity and the results wereWhich indicated whereby the high level of resistance at each of the antibiotics (CIP, AM, SXT, C, and NA) and the rate of (81%, 95%, 90%, 95% and 95% respectively), and the degree of high spirits at the level less than (0.01) at each of them. On the other hand, the results indicated the high level of sensitivity at each of the antibiotics (ATM, TE, IMP, and CF) and the rate of (100%, 100%, 100%, and 0.90, respectively), the distribution of the number of infected cases by sex and by The results of the injured males Mistoa the Top 13 (61.9%) compared with numbers from 8 females (38.1%), and the distribution of the number of infected cases by age group, which showed results with a rise in the age group (10 - 20).